Powell Lens-based Line-Scan Spectral Domain Optical Coherence Tomography for Cellular Resolution Imaging of Biological Tissues - Song, Weixiang (University of Waterloo, 2022)
A line-scan spectral-domain optical coherence tomography system was developed for corneal imaging. It utilizes a Powell lens to achieve a better line illumination power distribution than the conventional use of cylindrical lenses. It achieves a lateral resolution of <2.1 microns and ~4.1 microns in the x and y directions and an axial resolution of ~1.5 microns in tissue.
Keywords: optical coherence tomography, corneal imaging